PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA MANIPULATIF PADA SISWA SEKOLAH DASAR - Purwandi, Maman; Tampubolon, Budiman; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe the improvement of students’ learning outcome in learning cube and cuboid volume using manipulative media towards fifth grade students of Sekolah Dasar 14 Pereges Bengkayang. The method of this research is descriptive in form of classroom action research. The subject of this research is mathematics teacher and the fifth grade students, that is 24 students. Technique of data analysis used is observation and measurement. The tool of data collection is observation sheet and evaluation tests. Based on the data analysis, teacher’s ability on planning is 3.54 in the first cycle and 3.84 in the second cycle. Meanwhile, teacher’s ability on implementing is 3.39 in the first cycle and 3.91 in the second cycle. The students’ learning outcome is 25% in the first meeting and 87.5% in the second meeting of first cycle and 100% in both of meeting in the second cycle. In conclusion, manipulative media can improve mathematics learning of fifth grade students on the cube and cuboid volume material. Keywords: Learning Outcomes, Mathematics, Manipulative Media